Strategi Dan Implikasi Yang Tepat Pada Peningkatan Efektivitas Pembelajaran PAI - Tasya Fajriani; Putri Wulandari Nasution; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Indonesia requires Islamic Religious Education (PAI) as an important part in making students competent in cognitive, affective and psychomotor aspects (IQ and EQ). PAI functions to shape students' personalities so that they become virtuous and noble human beings (SQ). To increase competence in Islamic religious education, it is necessary to develop varied learning strategies. Varied learning strategies function to design learning methods and models, so that they are able to design teaching and learning environment systems and implement effectively and efficiently what has been planned in the learning objectives. Learning strategies are classified into 5 types: (1) direct learning strategies, (2) indirect learning strategies, (3) interactive learning strategies, (4) empirical learning strategies, (5) independent learning strategies.